Designing emotional support messages tailored to stressors. Issue 97 (January 2017) - Kindness, Peter; Masthoff, Judith; Mellish, Chris
Abstract: Although computers could offer emotional support as well as task support when aiding a user for a complex task, there is little current understanding of how they might do this. Moreover existing demonstrations of emotional support, though promising, only cover a small number of types of support and investigate a limited number of algorithms designed by hand. In this paper, we present an empirical investigation that starts from first principles, determining different categories of stressors for which emotional support might be useful, different categories of emotional support utterances and promising algorithms for deciding the content and form of textual emotional support messages according to the stressors present. At each stage, the results are validated through empirical experiments with human participants who, for instance, are required to place statements into categories, evaluate possible support messages in different imagined situations and compose their own emotional support from options offered. This development methodology allows us to avoid potentially challenging ethical issues in presenting people with stressful situations. Although our algorithms are attempting to choose emotional support based on the general, "naive" competence of human speakers, we use as a running example situations that can arise when attending a medical emergency and awaiting expert help. Abstract : Highlights: A set of scenarios that reliably express situations of a specific stressor. A set of emotional support statements reliably categorised into 5 main categories. An evaluated algorithm for choosing emotional support statements for a stressor. A method for investigating how to provide emotional support.